Chloramphenicol‐associated megaoesophagus in a dog. Issue 3 (31st July 2019) - Bishop, Bradley; Walton, Stuart
Abstract : A three‐year‐old spayed female Belgian malinois that was being treated with chloramphenicol for Corynebacterium ‐associated encrusted cystitis for seven weeks was evaluated for regurgitation, change in bark, hindlimb ataxia and anorexia. Thoracic radiographs revealed a severely, diffusely dilated oesophagus. Acetylcholine receptor antibody testing was negative. Chloramphenicol administration was discontinued and within five weeks of discontinuing the medication, the regurgitation ceased, ataxia resolved and appetite returned to normal. Thoracic radiographs were performed four months later revealing resolution of the previously observed megaoesophagus. This case suggests that chloramphenicol may be associated with the development of reversible megaoesophagus and peripheral neurotoxicity in dogs.